Impact of air pollution in paediatric consultations in Primary Health Care: Ecological study - Raquel Martín Martín; Marciano Sánchez Bayle (Elsevier, 2018)
Objective: To study the correlation between the levels of environmental pollutants and the number of paediatric consultations related to respiratory disease in Primary Health Care. Patients and methods: An ecological study is performed, in which the dependent variable analysed was the number of paediatric consultations in an urban Primary Health Care centre in Madrid over a 3 year period (2013-2015), and specifically the consultations related to bronchiolitis, recurrent bronchospasm, and upper respiratory diseases. The independent variables analysed were the levels of environmental pollutants. Coefficients of correlation and multiple lineal regressions were calculated. An analysis has been carried out comparing the average of paediatric consultations when the levels of nitrogen dioxide (NO2) were higher and lower than 40 μg/m3. Results: During the period of the study, there were a total of 52,322 paediatric consultations in the health centre, of which 6,473 (12.37%) were related to respiratory diseases. A positive correlation was found between SO2, CO, NOx and NO2 and benzene levels and paediatric consultations related to respiratory diseases, and a negative correlation with temperature. The number of consultations was significantly higher when NO2 levels exceeded 40 μg/m3. In the multiple lineal regression (P = .0001), the correlation was only positive between consultations and NO2 levels (3.630, 95% CI: 0.691-6.570), and negative with temperature (−5.957, 95% CI: −8.665 to −3.248). Conclusions: NO2 environmental pollution is related to an increase in respiratory diseases in children. Paediatricians should contribute to promote an improvement in urban air quality as a significant preventive measure. Resumen: Objetivo: Estudiar la relación existente entre los niveles de contaminantes ambientales y la demanda por enfermedad respiratoria en las consultas pediátricas de Atención Primaria. Pacientes y métodos: Estudio ecológico en el que la variable dependiente analizada ha sido la demanda en las consultas pediátricas de un centro de salud urbano de Madrid durante 3 años (2013-2015) por bronquiolitis, episodios de broncoespasmo y procesos respiratorios de vías altas. Como variables independientes se estudiaron los valores de contaminación ambiental. Se calcularon coeficientes de correlación y regresión lineal múltiple. Se comparó el promedio de consultas cuando los valores de dióxido de nitrógeno (NO2) eran superiores e inferiores a 40 μg/m3. Resultados: Durante el periodo de tiempo estudiado hubo un total de 52.322 consultas pediátricas en el centro de salud, de las cuales 6.473 (12,37%) lo fueron por procesos respiratorios. Se encontró correlación positiva entre los niveles de SO2, CO, NO2, NOx, benceno y el número de consultas por procesos respiratorios y negativa con la temperatura y el O3. El número de consultas por enfermedad respiratoria fue significativamente mayor cuando los niveles de NO2 superaban los 40 μg/m3. En la regresión lineal múltiple (p < 0,0001) solo se mantuvo la relación positiva de las consultas con los niveles de NO2 (3,630; IC 95%: 0,691-6,570) y negativa con la temperatura (−5,957; IC 95%: −8,665 a −3,248). Conclusiones: La contaminación ambiental por NO2 está relacionada con el aumento de la enfermedad respiratoria en la infancia. Los pediatras deberíamos contribuir a propiciar la mejora de la calidad del aire como una importante medida preventiva.